2019
DOI: 10.21315/eimj2018.10.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Coping Strategies among Undergraduate Nursing and Medical Students at American International Medical University, St Lucia

Abstract: Medical education can be highly stressful and could affect student performance and well-being. The present study was conducted to study stress and coping strategies among undergraduate medical and nursing students at a university in Saint Lucia. The study was conducted during July 2018 using the medical student stressor questionnaire (MSSQ) and the brief cope. The study was conducted using an online questionnaire. Gender, course of study, semester, nationality and age were noted. The stressors were grouped int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The low GPA mean score can be attributed to stressors as documented by Naidu et al in Trinidad which showed that “fear of failing course or year” and “examinations and fear of failing” were the highest-ranked stressors for dentistry students [ 26 ]. A study from St. Lucia [ 30 ] in the Caribbean region on stress and coping strategies among undergraduate medical and nursing students found that the commonly used coping strategies were active coping, positive reframing, planning and acceptance. Since medical education is very stressful, which could affect their health and well-being, there is a great need to study the stress and coping strategies among the medical and other health sciences.…”
Section: Discussionmentioning
confidence: 99%
“…The low GPA mean score can be attributed to stressors as documented by Naidu et al in Trinidad which showed that “fear of failing course or year” and “examinations and fear of failing” were the highest-ranked stressors for dentistry students [ 26 ]. A study from St. Lucia [ 30 ] in the Caribbean region on stress and coping strategies among undergraduate medical and nursing students found that the commonly used coping strategies were active coping, positive reframing, planning and acceptance. Since medical education is very stressful, which could affect their health and well-being, there is a great need to study the stress and coping strategies among the medical and other health sciences.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, a study on stress and coping strategies among undergraduate nursing and medical students by P Ravi Shankar et al (2018) also reported that the highest mean score is active emotional coping (M = 24.08), followed by problem-focused (M= 21.42) and avoidant coping (M = 18.90). This shows that emotion-focused coping is mostly chosen when dealing with stress.…”
Section: Discussionmentioning
confidence: 96%
“…The greater the use of active coping, the less the likelihood of having depression, as it can protect against the adverse effects of stress. Similar coping strategies were adopted by university and nursing students to avoid depression ( 37 38 ). It is noteworthy that the mean age for our study cohort was 63 years old and the mean duration of being a single mother was around 10 years.…”
Section: Discussionmentioning
confidence: 99%